Ecophysiological Traits May Explain the Abundance of Climbing Plant Species across the Light Gradient in a Temperate Rainforest - Gianoli, Ernesto; Saldaña, Alfredo; Jiménez-Castillo, Mylthon (PLOS ONE, 2012)
Climbing plants are a key component of rainforests, but mechanistic approaches to their distribution and abundance are scarce. In a southern temperate rainforest, we addressed whether the dominance of climbing plants across light environments is associated with the expression of ecophysiological traits. In mature forest and canopy gaps, we measured leaf size, specific leaf area, photosynthetic rate, and dark respiration in six of the most abundant woody vines. Mean values of traits and their phenotypic change (%) between mature forest and canopy gaps were predictor variables. Leaf size and specific leaf area were not significantly associated with climbing plant dominance. Variation in gas-exchange traits between mature forest and canopy gaps explained, at least partly, the dominance of climbers in this forest. A greater increase in photosynthetic rate and a lower increase in dark respiration rate when canopy openings occur were related to the success of climbing plant species. Dominant climbers showed a strategy of maximizing exploitation of resource availability but minimizing metabolic costs. Results may reflect phenotypic plasticity or genetic differentiation in ecophysiological traits between light environments. It is suggested that the dominant climbers in this temperate rainforest would be able to cope with forest clearings due to human activities.